2009
DOI: 10.1111/j.1364-3703.2009.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic production of nitric oxide in tomato responses to powdery mildew infection

Abstract: Various genetic and physiological aspects of resistance of Lycopersicon spp. to Oidium neolycopersici have been reported, but limited information is available on the molecular background of the plant-pathogen interaction. This article reports the changes in nitric oxide (NO) production in three Lycopersicon spp. genotypes which show different levels of resistance to tomato powdery mildew. NO production was determined in plant leaf extracts of L. esculentum cv. Amateur (susceptible), L. chmielewskii (moderately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 57 publications
1
44
0
1
Order By: Relevance
“…This finding might be related to a generally different extent and timing of transcript induction in the susceptible and resistant tomato genotypes. In our previous studies on these tomato genotypes, we also found differences in the extent and timing of the increased production of defence signalling molecules NO and H 2 O 2 during the time-course of powdery mildew invasion (Piterkova et al, 2009;Lebeda et al, 2014). The most remarkable difference between the genotypes studied was in the PR1 and germin-like protein classes (Fig.…”
Section: Comparison Of Basal Levels Of Defence Gene Transcriptsmentioning
confidence: 58%
See 1 more Smart Citation
“…This finding might be related to a generally different extent and timing of transcript induction in the susceptible and resistant tomato genotypes. In our previous studies on these tomato genotypes, we also found differences in the extent and timing of the increased production of defence signalling molecules NO and H 2 O 2 during the time-course of powdery mildew invasion (Piterkova et al, 2009;Lebeda et al, 2014). The most remarkable difference between the genotypes studied was in the PR1 and germin-like protein classes (Fig.…”
Section: Comparison Of Basal Levels Of Defence Gene Transcriptsmentioning
confidence: 58%
“…BABA represents a nonprotein amino acid generally accepted as a potent priming agent conferring increased resistance to biotic and abiotic stresses in many studied plants. As model tomato genotypes, we selected the previously well-characterized highly susceptible S. lycopersicum 'Amateur', representing a domesticated inbred cultivar, and S. habrochaites that exhibits a high non-specific resistance (Mieslerova et al, 2000;Tomankova et al, 2006;Piterkova et al, 2009Piterkova et al, , 2011Lebeda et al, 2014). The defence responses were monitored as transcript-level changes of selected genes with proven roles in non-specific resistance in tomato and model plants N. tabacum or A. thaliana.…”
Section: Discussionmentioning
confidence: 99%
“…The key role of NO as a signal molecule and in defence processes of plants was documented in the relationships of plants to wound reaction (Orozco-Cardenas and Ryan 2002) and interactions with viruses, bacteria, oomycetes (e.g. Sedlářová et al 2011) and fungi (Tada et al 2004;Prats et al 2005;Piterková et al 2009). NO is vital for initiation and development of a hypersensitive response in plants, modification of gene expression and synthesis of PR (pathogenesis related) proteins (Wendehenne et al 2004;Zeier et al 2004;Mur et al 2006;Zaninotto et al 2006).…”
Section: Involvement and Activity Of Antioxidant Enzymes In Plant Sysmentioning
confidence: 99%
“…Experiments focused on production of ROS were followed by study of production of reactive nitrogen species (RNS), mainly NO and NO synthase-like enzyme involved in local and systemic defence responses (Piterková et al 2009), using the same three genotypes of Solanum spp., which were used for the study of ROS production (Mlíčková et al 2004). In the susceptible genotype S. lycopersicum (L. esculentum) cv.…”
Section: Local and Systemic Production Of Nitric Oxide (No)mentioning
confidence: 99%
See 1 more Smart Citation